A novel combined Hib-MenC-TT glycoconjugate vaccine as a booster dose for toddlers: a phase 3 open randomised controlled trial - Pace, D; Snape, M; Westcar, S; Oluwalana, C; Yu, L; Begg, N; Wysocki, J; Czajka, H; Maechler, G; Boutriau, D; Pollard, A (BMJ Publishing Group, 2008)
Objective: To study the immunogenicity and reactogenicity of a combined Haemophilus influenzae type b and Neisseria meningitidis serogroup C tetanus toxoid conjugate vaccine (Hib-MenC-TT) when administered as a booster dose in combination with a measles, mumps and rubella vaccine (MMR). Design: A phase 3 open randomised controlled trial. Setting: One centre in Oxford, Uk and nine centres in Poland. Subjects: 12-15-month-old healthy children. Interventions: In the primary state of the study 500 healthy 6-12-week-old infants were randomised in a 3:1 ratio to receive Hib-MenC-TT+DTPa-IPV or MenC-CRM197 vaccine+DTPa-IPV-Hib. In the booster stage, 476 participants (190 in the UK and 286 in Poland) were vaccinated with Hib-MenC-TT and MMR. Main outcome measures: The proportion of children with protective serum antibody levels against MenC and Hib 6 weeks following a Hib-MenC-TT booster dose. Results: The co-primary objectives were met: the Hib-MenC-TT booster dose induced protective antibody titres in children vaccinated with Hib-MenC-TT+DTPa-IPV or MenC-CRM197+DTPa-IPV-Hib at 2, 3 and 4 months of age. 94.8% (lower limit of (LL) 95% CI 92.4) of participants had rSBA-MenC ≥1:128 and 100% (LL95% CI 99.2) achieved anti-PRP concentrations ≥ 1.0 μg/ml. The percentage of toddlers with a post boost rSBA-MenC of 1:128 was significantly higher after priming with Hib-MenC-TT (97.7%) than after MenC-CRM197 (86%) difference: 11.7%; 95% CI 6.2 to 19.4). Conclusion: The waning antibody titres against Hib and MenC following primary immunisation can be boosted to protective levels by administering the Hib-MenC-TT vaccine at 12-15 months of age, supporting the recent introduction of this vaccine in the UK immunisation schedule to sustain protection of children against Hib and MenC disease.